Quaternionic discrete series for Sp(1,1) - Seppänen, Henrik (MATHEMATICA SCANDINAVICA, 2009)
In this paper we study the analytic realization of the discrete series representations for the group G=Sp(1,1) as a subspace of the space of square integrable sections in a homogeneous vector bundle over the symmetric space G/K:=Sp(1,1) /(Sp(1) × Sp(1)). We use the Szegő map to give expressions for the restrictions of the K-types occurring in the representation spaces to the submanifold AK/K.